Intermolecular interactions in spinel structures. - Seguru, Grigory; Fertikov, Valery (European Journal of Applied Sciences, 2021)
Calculations of the electron concentration and compaction coefficients for the interaction of oxygen and metals that form oxides are presented. Calculations of the concentration of electrons and the compaction coefficients for the interaction of oxides forming spinel are presented. It is shown that the concentration of electrons and the concentration of nucleons are applicable to characterize the structures of substances. Correlation coefficients are calculated, indicating the relationship between the heat of reaction and the change in the volume of the reacting components.